Identification of Inorganic Waste in the Mangrove Ecosystem in Wara Timur and Bara District Palopo City - Wardayani, Wardayani; Mahmudin, Mahmudin; Sukimin, Ridwan (Journal of Coastal and Ocean Sciences, 2023)
One of the problems caused by human activities that many cities in the world face is marine debris. The emergence of some problems caused by an increase in the amount of waste is closely related to the increasing needs and human activities as the population increases. The purpose of this study was to determine the type of inorganic waste in the mangrove ecosystem in the Wara Timur and Bara Districts. This research was conducted in April - November 2023 in Wara Timur and Bara Districts. Meanwhile, the analysis of marine debris was carried out at the Marine Laboratory of the Muhammadiyah University of Palopo. Data collection techniques use the observation method by making a 100 long transect. In each District, 3 observation stations are made. The results of this study indicate that the types of inorganic waste found at the research location are plastic, glass, and cloth waste. Of the various types of waste obtained, plastic is the most common type of waste found in research locations.